Immunocytochemical utility of claudin‐4 versus those of Ber‐EP4 and MOC‐31 in effusion cytology. Issue 6 (26th March 2016) - Oda, Tomohiro; Ogata, Sho; Kawaguchi, Saki; Minabe, Shinya; Dokyu, Misaki; Takahashi, Hiromi; Kumazawa, Fumihiko; Shimazaki, Hideyuki; Takano, Masashi; Hase, Kazuo; Ozeki, Yuichi; Kanoh, Soichiro; et al.
Abstract : Background: Recently, claudin‐4 (CL4) immunocytochemistry was reported to be useful for differential diagnosis in effusion cytology. We wondered whether CL4 might be useful for "single‐shot" identification of metastatic carcinoma. The purpose of this study was to evaluate the usefulness of CL4 in effusion cytology. Methods: In total, 266 cases (169 metastatic carcinomas, eight malignant mesotheliomas, and 89 reactive mesothelial cells) were selected. Immunocytochemical examinations of cell‐block sections were performed for CL4, Ber‐EP4, and MOC‐31. We used an arbitrary 4‐tiered scale based on both staining intensity and positive‐cell percentage among all target cells, and calculated a staining index score (sum of the above two scores). Results: In a ROC‐curve analysis, higher area‐under‐curve values were found for CL4 than for Ber‐EP4 or MOC‐31 (0.982, 0.942, and 0.926, respectively). Conclusions: Since CL4 exhibited similar or superior usefulness to Ber‐EP4 and MOC‐31, it could become the first choice for the above differential diagnosis in effusion cytology. Diagn. Cytopathol. 2016;44:499–504. © 2016 Wiley Periodicals, Inc.